Increasing Capacity of Intersections with Transit Priority - Hao, Yanxi; Teng, Jing; Wang, Yinsong; Yang, Xiaoguang (Promet - Traffic&Transportation, 2016)
Dedicated bus lane (DBL) and transit signal priority (TSP) are two effective and low-cost ways of improving the reliability of transits. However, these strategies reduce the capacity of general traffic. This paper presents an integrated optimization (IO) model to improve the performance of intersections with dedicated bus lanes. The IO model integrated geometry layout, main-signal timing, pre-signal timing and transit priority. The optimization problem is formulated as a Mix-Integer-Non-Linear-Program (MINLP) that can be transformed into a Mix-Integer-Linear-Program (MILP) and then solved by the standard branch-and-bound technique. The applicability of the IO model is tested through numerical experiment under different intersection layouts and traffic demands. A VISSIM micro simulation model was developed and used to evaluate the performance of the proposed IO model. The test results indicate that the proposed model can increase the capacity and reduce the delay of general traffic when providing priority to buses.